A PERI-URBAN AREA: A RISK HOMETOWN FOR ELDERLY PEOPLE - Ungjitpaisarn, Worawut; Santasombat, Yos (Life Sciences and Environment Journal, 2020)
This qualitative research study investigated the situation of the local elderly people who lived in a peri-urban area in Chiang Mai. The purpose of this study was to understand such a situation of which the resultant changes affected the existence of the local elderly people. The relevant data of the study were collected through the notes taken during the observation of their everyday lives and the recordings of the casual conversations, direct inquiries, and in-depth interviews with 12 local elderly people, among which 6 were females and 6 were males, with their ages ranging between 60 and 75. It was found that the transformation of their rural area into a rural-urban area had an effect on the local elderly people, which caused them the risk of life’s insecurity in the social and economic dimensions resulting from the drop in or loss of the locally available resources that they would have otherwise benefited from. This study suggests that even though urbanization may introduce prosperity into a particular area, it is simultaneously very likely to subject the already vulnerable elderly people to the risk of life’s insecurity as such. Thus, risk to elderly people should be another important factor that needs to be taken into consideration when it comes to implementation of a development policy in a peri-urban area.